Protection for Heirs Who Don't Give Agreement To Transfer of Land Rights - Imamah, Okthika Nuril; Latumahina, Rosalinda Elsina (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
Study This use method study normative juridical is carried out with method examine and analyze something regulation law with approach regulation legislation and approach conceptual. The purpose of study This is for know How protection law for expert heirs who are not give agreement to transition right on land. For do transition right on land, the party who wants it do it must own agreement from expert other heirs. If there are lack agreement, transition right on land No allowed. Transition right on land without agreement expert the other heirs are activities that are not permitted in Indonesia. Regulation Indonesian law stipulates that transition right on land No allowed without agreement from expert other heirs. Result of study This is transition right on land inheritance without agreement expert inheritance is deed oppose legal and can cause loss for experts​ heirs who are not give agreement to transition right on land inheritance. This matter caused Because transition right on land legacy carried out without agreement all over expert inheritance No in accordance with regulation legal and can result conflict and dispute among experts​ heir.